Pre- and Post-Operative Pain Intensity and Physical Activity Levels in Individuals with Acetabular Dysplasia Undergoing Periacetabular Osteotomy: A Prospective Cohort Study - Naif Alrashdi; Robert Motl; Elroy Aguiar; Donald Lein Jr; Suzanne Perumean-Chaney; Michael Ryan; Matthew Ithurburn (International Journal of Sports Physical Therapy)
# Background